Including pupils with special educational needs and/or disabilities in mainstream secondary physical education: A revisit study. (May 2021) - Morley, David; Banks, Teresa; Haslingden, Craig; Kirk, Benjamin; Parkinson, Samatha; Van Rossum, Thomas; Morley, Imogen; Maher, Anthony
Our research used an innovative methodological approach by revisiting an original study conducted 15 years previously (Morley et al., 2005). A purposive sample of 31 secondary school teachers in the UK were interviewed to explore their perceptions of including pupils with special educational needs and/or disabilities (SEND) in mainstream secondary physical education (PE). All interviews were transcribed verbatim and texts analysed thematically. Findings suggest that, despite significant policy developments, little has changed in teachers' perceptions of their ability to include pupils with SEND in PE and there remain significant challenges to them achieving this. Some exceptions were documented, most notably an increased and positively received focus on inclusion within PE initial teacher education. The article concludes with recommendations for future practice, particularly in terms of teacher education and professional development, as well as the need for effective dissemination of research findings to key stakeholders.